Implementing RFID in China: A Critical Comparison between National and Foreign Owed Retailers - Wang, Luo (2011)
The research is aiming for discovering the issues in implementing RFID technology faced by the international and local retailers in China’s retailing industry. It is a comparative study, international and local retailers may have the same and different obstacles in implementing RFID technology, and those difficulties will be investigated and analysed through this study. Besides, whether it is worthy for the China’s retailers to invest in RFID technology for managing their supply chain will be investigated. Lastly, following by the analysis of the retailing industry and supply chain management issues in China, the future hypothesis of which (international or local retailers) is more capable to apply this technology earlier will be discussed. The study was done by the qualitative method and the primary data was generated by the interviews mainly, combined with the secondary data. Seven store managers in China’s retailing industry and two people out of the retail section were involved in the interviews. It is needs to be noticed that only three store managers’ interviews will use as the main source as they know much more about the RFID technology while other four managers do not understand the technology very well.